(untitled) (Jurnal Bahasa, 2025)
This paper presents aims to present an analysis of the linguistic history or development of the Malay dialects spoken in the interior regions of Kedah, specifically referring to the Baling Malay dialect. The discussion is divided into three main sections. The first part discusses the phonological system from proto-Malayic to the early Hulu Kedah Malay dialect. The second part explores the evolution of the early Hulu Kedah dialect into the current phonological system specifically of the Baling Malay dialect. In this context, “development” involves two fundamental concepts in diachronic linguistics: retention and innovation. The discussion also includes a third section addressing phonological processes throughout the history of the Hulu Kedah Malay dialect. Several phonological innovations and retentions in this dialect result in two significant implications. First, the Hulu Kedah dialect is distinct from the Northern Peninsular Malay dialect branch, meaning it is not a subdialect of the standard Kedah Malay. Second, due to its divergence from its traditional assumed parent dialect and its similarities with surrounding Malay dialects, Hulu Kedah Malay has formed its own branch, identified as the Upper Northen Peninsular Malay dialect branch. Keywords: Baling Malay dialect, dialectology, innovation, diachronic linguistic, Proto-Malayic, retention Full text: PDF